2023
DOI: 10.1007/s00442-023-05326-9
|View full text |Cite
|
Sign up to set email alerts
|

Consistent responses to moisture stress despite diverse growth forms within mountain fynbos communities

Abstract: Understanding climate change impacts on the Cape Floristic Region requires improved knowledge of plant physiological responses to the environment. Studies examining physiological responses of mountain fynbos have consisted of campaign-based measurements, capturing snapshots of plant water relations and photosynthesis. We examine conclusions drawn from prior studies by tracking in situ physiological responses of three species, representing dominant growth forms (proteoid, ericoid, restioid), over 2 years using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 48 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…Minimum water potentials for Cannomois acuminata (now C. parviflora) were measured as >À1.9 MPa between October to May at the same field site used for this study (Miller et al 1984;von Willert et al 1989). Similarly, a multi-year field ecophysiological investigation of the shallow-rooted C. congesta found that Ψ min never fell below À2 MPa, even in a particularly dry year, typically remaining >À1.2 MPa throughout the year (Skelton et al 2023). Gas exchange and sap flow were also maintained in these culms throughout the year, at relatively low levels (Skelton et al 2013;Skelton et al 2023), most likely sustained by the uptake of the regular dew and cloud moisture events during rain-free periods (Skelton et al 2023).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Minimum water potentials for Cannomois acuminata (now C. parviflora) were measured as >À1.9 MPa between October to May at the same field site used for this study (Miller et al 1984;von Willert et al 1989). Similarly, a multi-year field ecophysiological investigation of the shallow-rooted C. congesta found that Ψ min never fell below À2 MPa, even in a particularly dry year, typically remaining >À1.2 MPa throughout the year (Skelton et al 2023). Gas exchange and sap flow were also maintained in these culms throughout the year, at relatively low levels (Skelton et al 2013;Skelton et al 2023), most likely sustained by the uptake of the regular dew and cloud moisture events during rain-free periods (Skelton et al 2023).…”
Section: Discussionmentioning
confidence: 93%
“…Here we demonstrate that the optical and pneumatic methods can successfully generate robust estimates of vulnerability to embolism for restios, that will enable future examination of trait-environment relationships in this and other morphologically similar graminoid groups. Doing so allows us to demonstrate that restio occupancy of dry environments involves more than the evolution of highly resistant xylem, suggesting that other aspects of water relations are key to understanding trait-environment relationships in this diverse and ecologically important group (West et al 2012;Skelton et al 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, leaf-level gas exchange typically involves single-point measurements taken at infrequent intervals (several days) and is thus not suitable for continuous and long-term monitoring in the field. At the whole-plant level, sap flow is the most commonly applied method for continuous monitoring of transpiration, from which stomatal response to VPD can be inferred (Goulden & Field, 1994;Hogg & Hurdle, 1997;Motzer et al, 2005;Skelton et al, 2013Skelton et al, , 2023. However, there are several issues that limit the resolution of sap flow data for assessing the dynamic regulation of stomatal conductance.…”
mentioning
confidence: 99%